The competence approach as the basis to form training system for library professionals in the Republic of Cameroon - J. Zemengue; T. Mbila (Библиосфера, 2019)
The article deals with the attitude of specialists to the competence approach in higher education, the stages of the “competence” formation concept are shown. The authors share the point of view of specialists, who emphasize the practical orientation of competences, and the competence approach itself is based on the practical orientation of education. After the analysis of publications, the authors come to the conclusion that the training of librarians in the Republic of Cameroon should ensure the formation of the following three groups of competences: 1) academic competencies, including basic knowledge and skills; 2) social and personal competences, including cultural and value orientations connected with the attitude of a person to himself as a personality (personal competence) and related to the person as a subject of interpersonal communication (communicative competence); 3) professional competencies. The authors show the basic technological competences required by Cameroonian library staff and believe that they should be incorporated into special academic disciplines and curricula of the department of documentary information. The authors conclude that academic, socio-personal and professional competences should be the basis not only for the educational standard of higher library education (getting bachelor’s and master’s degrees), which should be developed in Cameroon, but also for the entire system of training of highly qualified library personnel in the country.